Effect of level of lactic acid bacteria inoculant from fermented grass extract on fermentation quality of king grass silage - Antaribaba, M.A; Tero, N.K; Hariadi, B. TJ.; Santoso, B. (Indonesian Journal of Animal and Veterinary Sciences, 2009)
Ensiling is a method of preserving moist forage based on natural fermentation where lactic acid bacteria (LAB) ferment water soluble carbohydrate into organic acids mainly lactic acid under anaerobic condition. The aim of this study was to evaluate the quality of king grass (Pennisetum purpureophoides) ensiled with addition of LAB prepared from fermented grass extract (LBFG). Four treatment were (G0) king grass without additive; (G1) king grass with 2% (v/w) of LBFG; (G2) king grass with 3% (v/w) of LBFG; (G3) king grass with 4% (v/w) of LBFG. Ensiling was conducted in bottle silos of 225 g capacity at room temperatures (27.0 Â± 0.20C) for 30 days. The results showed that crude protein content in silage G1, G2 and G3 were relatively higher than that in silage G0. The pH value, butyric acid, total VFA and NH3-N concentrations decreased linearly with increasing level of LBFG addition, while lactic acid concentration increased linearly with LBFG addition. It was concluded that addition of 3% (v/w) of LBFG resulting a better fermentation quality of king grass silage than 2% and 4% (v/w) of LBFG. Key words: Silage, Lactic Acid, Fermentation, King Grass